Scar Endometriosis - Rai, Snigdha; Khadka, Shailaja; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Scar endometriosis following caesarean section is a rare presentation and is characterized by the presence of endometrial glands implants at the incision site. As the patients present with a lump in the abdominal scar, the preoperative diagnosis can be often mistaken with other surgical conditions. We present two cases of post cesarean scar endometriosis. Cyclical pain and scar lump were evaluated both clinically and sonologically; then confirmed by excision biopsy.